Sombreamento e fertilização nitrogenada sobre atributos de solos e produtivos da Brachiaria Brizantha cv. Marandu - Guilherme Lanna Reis (2011)
This study assessed the influence of nitrogen fertilization and artificial shade on the attributes of soil and forage in a pasture of Brachiaria brizantha cv Marandu (BBM). The experiment was conducted at Fazenda Águas Formosas in Caeté, Minas Gerais State, Brazil, 19º4739S,43º36'77''W, altitude 1000 m. The soil is a Red latosol by the Brazilian soil classification (Typic Acrustox - USDA classification). BBM was subjected to four levels of fertilization (0, 50, 70 and 100 kg N per hectare per application) and four levels of shading (0, 47, 53 and 66%) through a nylon mesh. Shading reduced the mineralization of organic matter, affecting the lower availability of complexed nutrients. N application favored the exportation of most nutrients assessed. Nutrient content tended to decrease with depth. Shading factors, N rate and season influenced the productive characters of forage. BBM dry matter production (DMP) increase correlated with N rate and luminosity increase. For the addition of each kg of N per hectare per application and 1% reduction in shadding, there was an increase in DMP of approximately 0.5%. From these data, one can make the choice of a production system in terms of shading and nitrogen fertilization that is more feasible both economically and environmentally